(untitled) (Fiep Bulletin - online, 2011)
The aim of this study was to research the level of knowledge of physical education professionals and educators of the public and private schools of the city of Tangará-MT towards tooth avulsion and the procedures of reimplant, raising a holistic view through information, contributing to save the tooth. Since the practice of sport in schools contribute to an increasing prevalence of dental trauma, these professionals surveyed are closely related to the vctims of dental avulsion and do not have the necessary knowledge to provide first aid and perform dental reimplantation and not contributing to a favorable prognosis. It was interviewed 130 teachers through a multiple choice questionnaire, focusing on the knowledge of immediate help in cases of dental avulsion. The data showed that 72% of interviewed. did not know what is avulsion. Regarding the storage way of avulsed tooth, milk was elected by 30% of respondents as the best means of storage, but the saline solution is the most suitable being chosen by only 7% of interviewed. 93% of teachers would be unable to reimplant the avulsed tooth correctly aswell they would not know how to get the tooth, and 50% would take the tooth anyway, being most indicated pick up the tooth by the crown with 41% of interviewed. We conclude that the majority of interviewed unaware the dental avulsion in sport and reimplantation procedures, as well as the approach to victims of avulsion. The interviewers also find it important to have in their academic information about the topic since most have never received any information which would help save the tooth.